IMPLEMENTASI METODE SOROGAN DALAM KEBERHASILAN MEMBACA KITAB KUNING DI PONPES DAARUS SA’ADAH II COGREG - Akhmad Fatihur Rokhmat; Rio Prasetio; Ika Ika (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2022)
The purpose of this study was to find out the results of the implementation of the sorogan method in the success of reading “Kitab Kuning” at Ponpes Daarus Sa'adah II. The method of data collection in this research is qualitative research with interview, observation, and documentation methods. The way it works is that the researcher collects data both primary in nature where the data is obtained directly from the source, as well as secondary data obtained through reading previous thesis, books and others. The implementation of the sorogan method in reading “Kitab Kuning” can be classified into several parts, including: Senior students in this case are service students, class XI MA, and XII MA students, sorogan goes directly to Putra Kyai, while the implementation time is once every two weeks on Friday nights. Saturday and Saturday evenings are held in front of the kyai's house, while the junior students of class VII SMP deposit memorization murodah or language vocabulary, class VIII SMP to class X sorogan to senior students which is carried out on Tuesday at 14:00 WIB. The implication of sorogan is very effective in learning “Kitab Kuning”, especially in the success of reading “Kitab Kuning”. Because in this sorogan method, students are required to be more active and critical, it also demands perseverance from students. From the results of the tests, interviews and observations above, it can be concluded that the sorogan method is quite effective in successfully reading “Kitab Kuning”